Economic Well-Being from Steve Hank's Point of View / Iraq as a Model for the Period (2004-2020) - Mazen Sultan Azyz; Muhammed Hussan Aaodh (Kurdish Studies, 2023)
The research seeks to analyze the indicators of approaching economic prosperity in Iraq for the period (2004-2020), from the point of view of economist Steve Hanke from the American Johns Hopkins University, which includes the targets of monetary and financial policies: growth in real per capita output, and inflation and unemployment equations—the nominal interest (or policy rate). The inductive approach - descriptive Analysis was adopted in the research method using Iraqi data from the Ministry of Planning and the Central Bank. The research results were the continued dependence of the most significant proportion of actual per capita output growth on fluctuations in global crude oil markets and the high performance of monetary policy in reducing inflationary pressures through its non-existent tools. Direct and with the cheerful help of net foreign assets and closing the merchandise deficit from imports, the focus of fiscal policy on reducing the disparity in income distribution by increasing the employment of the unemployed in the government sector and deepening disguised unemployment, the link between the effectiveness of monetary and fiscal policies in achieving economic well-being with the unsustainability of growth in real per capita output and the relative rise In the unemployment rate, they are two aspects of the distortion of the structure of the Iraqi economy. The study concluded that it is critical to concentrate macroeconomic policy, particularly its monetary and financial tools, on diversifying the Iraqi economy to maintain the rise in real income for each and distributive justice for employment. This is also necessary to sustain economic well-being, the central bank's independence, and its ability to respond to the market by balancing the need to rein in inflation with the promotion of investment and reorganizing the commercial banking sector to boost and expand the economy of Iraq.